Graphical Analyzer Test of Misconception of 45o Angle as Optimal Angle in Projectile Motion - Purnama, Riki; Andhika, Shidiq; Nurul, Annisa Fitriani; Cesariyanti, Yunissa; Agustina, Rena Denya (Radiasi : Jurnal Berkala Pendidikan Fisika, 2024)
Misconceptions still often occur when learning physics, especially in conducting research that is not consistently detailed in identifying an observation. In parabolic motion material, it is known that 45° is a special angle that produces the farthest distance. The misconception that 45° is the angle that produces the farthest distance has become a reference in learning in various educational institutions to date. The aim of this research is to identify and prove that the 45° angle is not an elevation angle that produces the farthest distance in a vacuum that ignores the initial position of the thrower. This research was conducted using PhET virtual laboratory media which was analyzed based on quantitative and qualitative methods. This study will test the elevation angle of 42° : 45° : 48° based on altitude 0 m : 1 m : 2 m. After the observational data has been obtained and proven by the existing equations, the research results will be analyzed based on the functional analyzer approach by making the equations into function graphs to make it easier for readers to read the existing data. In this study, it was found that the angle of 42° is the producer of the farthest distance and also gets a relatively faster travel time compared to the angle of 45° which we know so far as a special angle that produces the farthest distance in non-vacuum conditions.